2010
DOI: 10.1007/s10592-010-0062-3
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity, spatial dynamics, and small genetic population size in the rare sunflower, Helianthus verticillatus

Abstract: Knowledge of population size is an important step for identifying populations of immediate conservation concern. However, this task is difficult in plant species that exhibit clonal growth, since a simple ''head count'' may not be appropriate. Here, I determine the genetic population size and the extent of clonality in the four known populations of a rare sunflower, Helianthus verticillatus. Previous work in this species revealed high genetic diversity in all populations but significant fitness differences amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 24 publications
4
27
0
Order By: Relevance
“…The whorled sunflower, Helianthus verticillatus Small, is a rare and federally endangered plant (U.S. Fish and Wildlife Service, 2014) found in only a few locations in the southern United States. This plant was described in 1892 by Samuel Bain (Ellis et al, 2006;Mandel, 2010;Matthews et al, 2002;Small, 1898) from collections obtained in Chester County, TN. The species was not collected again until 1993, when it was discovered in Floyd County, GA (Matthews et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The whorled sunflower, Helianthus verticillatus Small, is a rare and federally endangered plant (U.S. Fish and Wildlife Service, 2014) found in only a few locations in the southern United States. This plant was described in 1892 by Samuel Bain (Ellis et al, 2006;Mandel, 2010;Matthews et al, 2002;Small, 1898) from collections obtained in Chester County, TN. The species was not collected again until 1993, when it was discovered in Floyd County, GA (Matthews et al, 2002).…”
mentioning
confidence: 99%
“…Helianthus verticillatus are 2-to 4-m-tall plants that produce flowers from late August or early September to mid-October (Matthews et al, 2002) or until a killing frost. This sunflower is a self-incompatible and largely insectpollinated species (R. Trigiano, unpublished data) that does not lend itself to wind pollination (Mandel, 2010). Pollinators of H. verticillatus and other self-incompatible plants are likely restricted to the flight range of locally available insect visitors (Ackerman, 2000;Faegri and Leendert, 1966).…”
mentioning
confidence: 99%
“…Ellis et al (2006) rejected the hypothesis that H. verticillatus was a hybrid, thus proposing that the plant was a distinct species. Further research focusing solely on this plant found high clonal diversity, despite predominate vegetative reproduction (Mandel, 2010). Moreover, there were far fewer distinct genetic individuals than previously thought (Ellis et al, 2006;Mandel, 2010).…”
Section: Introductionmentioning
confidence: 61%
“…Further research focusing solely on this plant found high clonal diversity, despite predominate vegetative reproduction (Mandel, 2010). Moreover, there were far fewer distinct genetic individuals than previously thought (Ellis et al, 2006;Mandel, 2010). Additional studies on H. verticillatus have indicated very apparent differences in fitness among populations (Mandel, 2010;Ellis et al, 2006Ellis et al, , 2008Ellis and McCauley, 2009).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation